Methodological Foundations and Problems of the Study of Political Capacity of Local Government in Russia: Preconditions and Circumstances for the Formulation of Basic Theoretical Models (part one) - S. N. Baranets (Управленческое консультирование)
The article offers an author’s view on the prerequisites and difficulties of finding methodological grounds for investigating the problem of deploying the political potential of local power in modern Russia. The text of the publication reveals and formulates the main range of issues that need to be disclosed to explicate the author’s vision of the prospects for realizing the opportunities for interaction of local authorities, as a will to self-organize the population of territorial loci, and the forms in which they objectively exist today in accordance with the current legislation of the Russian Federation . It is shown how the spontaneous accumulation of the political potential of local self-government in modern conditions can be beyond the regulatory management impact of state authorities and management, and in this connection, the thesis is based on the inadequacy of modern ways of recording and controlling the conditions and results of the activities of the generative centers of democratic democracy in the local Scale. An attempt was made to substantiate a number of intermediate conclusions regarding the author’s proposed research program in the problem of local government administration and its potentialities, and outlined prospective directions for further study of the identified problematic issues.